The rise of noncommunicable diseases in Latin America and the Caribbean: Challenges for public health policies - Maria Victoria Anauati; Sebastian Galiani; Federico Weinschelbaum (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2015)
The health landscape in Latin America and the Caribbean is changing quickly. The region is undergoing a demographic and epidemiological transition in which health problems are highly concentrated on noncommunicable diseases (NCDs). In light of this, the region faces two main challenges: (1) develop cost-effective policies to prevent NCD risk factors, and (2) increase access to quality healthcare in a scenario in which a large share of the labor force is employed in the informal sector. This paper describes both alternative interventions to expand health insurance coverage and their tradeoff with labor informality and moral hazard problems. The paper also focuses on obesity as a case example of a NCD, and emphasizes how lack of knowledge along with self-control problems would lead people to make suboptimal decisions related to food consumption, which may later manifest in obesity problems.
Keywords: I12; I13; I18; 330; Noncommunicable diseases; obesity; health insurance